Comment on “A randomized double-blind trial of intranasal dexmedetomidine versus intranasal esketamine for procedural sedation and analgesia in young children” - Jiajing Wang (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract This comment critiques a trial comparing intranasal dexmedetomidine (DEX) and esketamine (sKET) for pediatric procedural sedation. Despite a large effect size, the small sample (n = 29) likely caused false-negative results (p = 0.09), necessitating larger trials. Safety concerns (e.g., aspiration risk), unaddressed long-term psychological outcomes, and limited pharmacokinetic data (delayed DEX onset, prolonged duration) challenge clinical applicability. Future studies should integrate objective measures and long-term follow-up.